2003
DOI: 10.1021/jp036196h
|View full text |Cite
|
Sign up to set email alerts
|

18-Crown-6 and Its Hydrates:  Bridging but Versatile Hydrogen Bonding. A Theoretical Study of Static and Dynamic Properties

Abstract: Quantum chemical (QM), classical molecular dynamics (MD), and Car-Parrinello (CP-MD) studies are reported for 18-crown-6 (18C6) and its first 18C6(H 2 O) n hydrates, focusing on the D 3d and C i forms of the crown. They reveal the importance of dynamics and the surrounding medium on its conformational and hydrogen-bonding properties. In the gas phase, the two forms of the free crown are found to be quasi-isoenergetic at several computational levels, but during CP-MD simulations, the D 3d form is more mobile th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2005
2005
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(24 citation statements)
references
References 51 publications
0
24
0
Order By: Relevance
“…The low internal energies limit the degree to which these species can surmount barriers to rearrangement to lower energy structures, and thus higher energy conformers may be trapped. This seems to be the case in the B conformer where the neutral bidentate (18c6)H 2 O, mentioned earlier [15] as one of the preferred configurations for the monohydrated neutral system, may first be formed in the argon cluster with a sufficient barrier for K + to replace the bidentate H 2 O inside the 18c6 cavity. We performed DFT calculations on the neutral (18c6)H 2 O system to gain insight on the B conformer, since the aforementioned hydrated alkali metal ion systems [18] showed that the high energy conformers, trapped in our previous experiments, mirror robust neutral structures that failed to undergo rearrangement after ion impact.…”
Section: Resultsmentioning
confidence: 83%
See 1 more Smart Citation
“…The low internal energies limit the degree to which these species can surmount barriers to rearrangement to lower energy structures, and thus higher energy conformers may be trapped. This seems to be the case in the B conformer where the neutral bidentate (18c6)H 2 O, mentioned earlier [15] as one of the preferred configurations for the monohydrated neutral system, may first be formed in the argon cluster with a sufficient barrier for K + to replace the bidentate H 2 O inside the 18c6 cavity. We performed DFT calculations on the neutral (18c6)H 2 O system to gain insight on the B conformer, since the aforementioned hydrated alkali metal ion systems [18] showed that the high energy conformers, trapped in our previous experiments, mirror robust neutral structures that failed to undergo rearrangement after ion impact.…”
Section: Resultsmentioning
confidence: 83%
“…Further calculation details are available in supporting information section. Previous theoretical work [15] indicates that there are three low lying conformations for 18c6(H 2 O), two of which feature single hydrogen bonds and one with a bidentate hydrogen-bonded water. In K + (18c6)(H 2 O), previous ab initio calculations by Feller [10] indicate that the most favored configuration features K + nestled inside the 18c6 cavity with H 2 O coordinated to K + and forming a hydrogen bond with one 18c6 oxygen.…”
Section: Calculationsmentioning
confidence: 98%
“…To the best of our knowledge no QM studies of the complexation of Na + and diaza-18-crown-6 have been reported but many simulation studies have been made involving the complexation of crown ethers and their derivatives with ions. Many insights into the complexation and conformation of the crown ethers have been previously gained by quantum mechanical [24][25][26][27][28][29][30][31][32][33][34][35][36][37][38] and force eld simulations. [39][40][41][42][43][44][45][46][47][48][49][50][51][52][53][54] These studies, due to the similarity of 18-crown-6 to the diaza-18-crown-6, provide us with a point of reference for comparison.…”
Section: Introductionmentioning
confidence: 99%
“…The wings link to the water molecule O9 via hydrogen bonds (Table 2), and the water molecules also hydrogen bond to the crown ether O atoms, stabilizing the extensive sandwich array of Cu(H 2 NTA)-(H 2 O)Cl units between successive macrocyclic 18-crown-6ether units. Every 18-crown-6-ether ligand associated with two water molecules on opposite sides adopts the conventional conformation with pseudo-D 3d symmetry (Schurhammer et al, 2003). This gives rise to a hydrogen-bonded one-dimensional chain with a succession of Cu(H 2 NTA)(H 2 O)Cl, H 2 O and 18crown-6 molecules.…”
Section: Commentmentioning
confidence: 99%